A comparison of women’s position in the Tasnim Exegesis of the Qur’an and the Convention on the Elimination of all forms of Discrimination Against Women and the 2030 Education Framework - Yahya Jahanghiri; Khadijeh Ahmadi Bighash (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2021)
From the view point of creation, there are without doubt subtle differences between men and women. Islam has given an exalted and lofty dignity to women with a definite attitude that considers all of her rights and characteristics. However, there is a balance suiting her dignified and innate nature between both her rights and her obligations in Islam. In recent decades, the issue of women as a global issue has been considered by international declarations such as the “Convention on the Elimination of Discrimination Against Women” and the “2030 Education Framework”, whose main nature is to create a kind of complete similarity between man and woman based on gender; which in this case sets requirements for nations and governments. This research has employed descriptive and text analysis methods as well as library and field research methods to do a comparative study on international documents and the articles of these treaties. To do this, it will use verses of the Qur’an that talk about women’s rights and refer to the Tasnim exegesis of the Qur’an written by Ayatollah Javadi Amooli. The Tasnim exegesis of the Qur’an has recognized rights such as the right to development, theological rights, the right to motherhood and wifehood, economic rights, political rights, social rights, family rights and spiritual rights, etc. as women’s indisputable rights.